Assembling metallic 1T-MoS2 nanosheets with inorganic-ligand stabilized quantum dots for exceptional solar hydrogen evolution. Issue 41 (21st April 2017) - Li, Xu-Bing; Gao, Yu-Ji; Wu, Hao-Lin; Wang, Yang; Guo, Qing; Huang, Mao-Yong; Chen, Bin; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : Metallic 1T-MoS2 nanosheets are firstly assembled with inorganic-ligand stabilized QDs for enhanced solar H2 evolution. Abstract : Due to their enhanced light harvesting, favored interfacial charge transfer and excellent proton reduction activity, hybrid photocatalysts of metallic 1T-MoS2 nanosheets and inorganic-ligand stabilized CdSe/ZnS QDs obtained via a self-assembly approach can produce H2 gas with a rate of ∼155 ± 3.5 μmol h −1 mg −1 under visible-light irradiation ( λ = 410 nm), the most exceptional performance of solar H2 evolution using MoS2 as a cocatalyst known to date.